Legal Protection for Child Victims of Sexual Violence: A Case Study of an Elementary School Student in Gandus - Saputri, Emilia Dian; Saputra, Adit Aril; Raditya, M. Fadhil; Santika, Juwita; Januarti, Aisyah Putri; Aldo (Yayasan Bina Lentera Insan, 2026)
This study aims to analyze the forms of legal protection for child victims of sexual violence, its implementation in the case of an elementary school student in Gandus District, and efforts to optimize legal protection for victims. The research employed a normative legal method using statutory and case approaches. Data were collected through a library research technique by examining laws and regulations, books, journals, and other relevant literature. The results indicate that legal protection for child victims of sexual violence is carried out through pre-emptive, preventive, and repressive measures. In the Gandus case, legal protection was implemented through law enforcement against the perpetrator, victim assistance, and psychological recovery efforts. The optimization of legal protection can be achieved through strengthening preventive measures, providing legal aid and victim assistance, and developing integrated services to ensure effective protection and recovery for victims.